1990
DOI: 10.1080/03014469000000862
|View full text |Cite
|
Sign up to set email alerts
|

Skin colour data from Nowshahr City, Northern Iran

Abstract: Skin colour data from the population of Nowshahr City, northern Iran, reveal significant differences between the males and females on the upper inner arm and the forehead, and within each sex between the sites. Pigmentary variation in association with pubertal age is not found to be statistically significant. Close affinities in pigmentation with some neighbouring populations are also assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…Yet, within individual ethnic groups, men have been reported to have darker and less reflective complexions [30][31][32]. It has been suggested that this is the consequence of men having a more vascularized upper dermis [26] and more melanin [33,34]. These differences could have hormonal causes because they arise during puberty and also increase with age [35].…”
Section: Skin Tonementioning
confidence: 98%
“…Yet, within individual ethnic groups, men have been reported to have darker and less reflective complexions [30][31][32]. It has been suggested that this is the consequence of men having a more vascularized upper dermis [26] and more melanin [33,34]. These differences could have hormonal causes because they arise during puberty and also increase with age [35].…”
Section: Skin Tonementioning
confidence: 98%
“…A large proportion of inhabitants of Ardabil are Azeri (also of Caucasian ancestry). The average skin pigmentation of people living in these provinces is light, showing affinities with less pigmented populations residing in neighboring countries to the West of Iran (Mehrai and Sunderland, 1990). The province of Kerman is located in southeastern Iran with dry moderate climate in the north of the province and warm and humid in the south.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism in skin color has been reported, with females tending to have lighter skin color than males after puberty (Cartwright, 1975; Clark et al, 1981; Jaswal, 1983; Frost, 1988; Mehrai and Sunderland, 1990; Williams-Blangero and Blangero, 1991). Lightening of skin color is reported to occur during puberty in both sexes, but the process is less noticeable in males, so that females are lighter than males in adulthood (Mesa, 1983).…”
Section: Discussionmentioning
confidence: 99%